Evaluating Baseflow Simulation in the National Water Model: A Case Study in the Northern High Plains Region, USA. (15th March 2021) - Karki, Ritesh; Krienert, Joseph M.; Hong, Minki; Steward, David R.
Abstract: The National Water Model (NWM) is a high‐resolution hydrological model capable of providing streamflow forecast at 2.7 million reaches across the conterminous United States (U.S.). It utilizes a conceptual (not physically explicit) module for estimating groundwater discharge (baseflow) to streams, and the baseflow module only allows for one‐way flux from the aquifer to the streams, with no interflow between surficial or groundwater catchments. This study evaluated the ability of the NWM to simulate baseflow in different geologic conditions with a case study in the Northern High Plains region. The study also evaluated two alternative formulations for the baseflow module in the NWM with the goal of improving simulated baseflow accuracy. The NWM simulated baseflow more accurately in a clayey catchment than in a sandy catchment. The model, however, over simulated baseflow during storm runoff events and under simulated during low flow events in both catchments. Analysis of groundwater recharge simulation showed that the NWM over simulated groundwater recharge for both catchment types, and reducing groundwater recharge using U.S. Geological Survey Baseflow Indexes improved the model performance for baseflow simulation, especially in the sandy catchment. Evaluation of the alteranative formulations showed that a modified Rorabaugh‐Rutledge formulation was able to improve the baseflow simulation with RMSE of 7.98 m 3 /s and R 2 of 0.41 and also improved the timing of peak flows. Abstract : Research Impact Statement : Assessment of baseflow simulation in the National Water Model and evaluating alternative functions to provide improved physical representation using a case study in the Northern High Plains region.